Wafer Level Packaging for MEMS Geiger Counter - Miyamoto, Asei; Hashimoto, Taichi; Makimura, Kenichi; Kanda, Kensuke; Fujita, Takayuki; Maenaka, Kazusuke (2012 Fifth International Conference on Emerging Trends in Engineering and Technology, 2012)
The size of conventional Geiger counters is large because the detector (GM tubes: Geiger muller tubes) is fabricated by mechanical processing. In this paper, an MEMS (micro electro mechanical systems) GM tube using a wafer level packaging is proposed. The MEMS-GM tube with glass/Si/glass stacked structure was fabricated by using anodic bonding and polymer bonding. With the supplied voltage of 2.6 kV to the MEMS-GM tube, pulse waves were observed when an radioactive material approached to the fabricated device.